PERSEPSI MASYARAKAT TENTANG KEPEMILIKAN AKTA KELAHIRAN DI KEPENGHULUAN KOTA PARET KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR - Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Lack of information and socialitation given in Kepenghuluan Kota Paret,leads to a lack of understanding about the infortance of having a birth certificate in daily life cause in lower public interest to register the population documents especially birth certificate. Not a few of them who use the services of pander or asked employees Kepenghuluan to take care of their birth certificate with the administrative coasts are more expensive than it should.In this research the concept of the theory used is proposed by Miftah Thoha,about how a perception can be seen from the four subprocesses,are: 1.Stimulation / Present situation 2.Registration 3.Interpretation 4.Feed Back. In his theory,Miftah Thoha suggests are several factors that imfluance a person’s perception.,are: 1.Psychology 2.Family 3.Culture. The location of the research was conducted in Kepenghuluan Kota Paret Region Simpang Kanan Districts Rokan Hilir. In this research, the researchersin used qualitative research methods to study descriptive data.In the data collection,researchers used interview, observation and documentation.By using keyinforman as a source of information. And to got the informan,the researchers using Snowball Sampling method.The results of this research can concluded that the Public Perception About The Birth Certificate Of Ownership In Kepenghuluan Kota Paret Region Simpang Kanan Districts Rokan Hilir is not good. Therefore expected to governments region Simpang Kanan Districts Rokan Hilir especially Kepenghuluan Kota Paret to provide insight to the entire public,about the importance of having a birth certificate for everyone, and provide services that are cheap,fast and friendly, so that people are not lazy to take care of their birth certificate.Key Words : Perception, Public, Birth Certificate